Extraction of DNA from Sperm Cells in Mixed Stain by Nylon Membrane Bushing Separation Technique - MA Jun, TONG Qi, GAO Liang-bi，et al. (Fayixue Zazhi, 2018)
Objective To establish a novel method for the separation of sperm cells in mixed stain, and to evaluate its application value. Methods Totally 40 mixed stain samples were collected from sexual assault cases. Sperm cells were separated by the conventional differential lysis method and the nylon membrane bushing separation technique, respectively. The DNA of sperm cells was extracted with the silicon membrane kit （Forensic DNA Extraction Kit for Soft Tissues）. The PCR amplification was performed using AmpF?詛STR?誖Identifiler?誖Plus kit, and the products were electrophoresed by 3500xL genetic analyser. The results of two separation methods were then compared. Results Complete and single-source male STR genotypes could be obtained from all the 40 mixed stain samples except three samples with minimal residual of female DNA by the nylon membrane bushing separation technique. The STR genotypes of sperm cells could not be detected in 25 samples, which were obtained in 15 samples （seven were of incomplete male STR genotypes, six with residual of female DNA, two were complete and single-source STR genotypes of sperm cells）. Conclusion The nylon membrane bushing separation technique developed in present study can be used in the separation of sperm cells in mixed stain, especially for the extraction of a small amount of sperm from a large quantity of female cells, which is inexpensive, rapid and simple.